Effect of UDP traffic on TCP’s round-trip delay - Hai-ting ZHU; Wei DING; Li-hua MIAO; Jian GONG (Tongxin xuebao)
A single link-oriented TCP transmission performance metric called “R”was proposed.The relationship between metric R and two indicators (the utilized link bandwidth and the UDP traffic proportion) on the same link was analyzed,and the experiment results on passive measurement datasets from two bidirectional network links separately located in USA and China were laid out.The results show that the metric can be expressed as a normally distributed sto-R chastic process with distinct parameters decided by the utilized bandwidth and the UDP traffic proportion.Further,by using fitting methods on local datasets,a concrete function,which was acceptable at a high confidence level,was given to describe the relationship between the mean value of R 's normal distribution and the two indicators mentioned before.This work offers a reference to the study of network fairness.